Pharmakotherapie des Schmerzes bei älteren Patienten mit Nichtopioiden = Non-opioid pain medication in the elderly - Burkhardt, Heinrich; Wehling, Martin (Der Schmerz, 2015)
Non-opioid analgesics are frequently used to control chronic pain in elderly patients; however some of these drugs show high rates of adverse drug reactions. Among these are significant clinical problems which impede an effective and safe pain control. This review provides recent data concerning non-steroidal anti-inflammatory drugs (NSAID), acetaminophen, metamizol and flupirtin. Due to their risk profile NSAIDs are less appropriate due to high incidence rates and drug-related risk patterns. Acetaminophen, metamizol and flupirtin may be recommended instead; however a shortcoming of acetaminophen in comparison to NSAIDs is its weaker action to control pain. Metamizol is still banned in some countries due to rare but potentially severe hematological side effects and flupirtin frequently causes unfavorable sedation.